ANALYSIS OF FACTORS AFFECTING SELF MANAGEMENT IN TYPE 2 DIABETES MELLITUS PATIENTS - Ceria Nurhayati; Nur Hidayanti; Ninik Ambar Sari; Sri Anik Rustini (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Diabetes mellitus type 2 is a common problem that occurs in people who have metabolic disorders characterized by increased blood sugar due to decreased secretion by pancreatic beta cells or impaired insulin function. Objectives: This study aims to determine what factors are associated with self-management in Type 2 DM patients at the Buduran Health Center.Design: This study was a quantitative research. The design in this study was a cross-sectional analytic with a sample of 80 people who were carried out at the endocrine polyclinic Puskesmas Buduran Sidoarjo. Research instrument used the Diabetes Self-Management Questionnaire (DSMQ) developed by Schmitt et al (2013) to determine the self-management of type 2 DM patients and to measure the level of knowledge using the Diabetes Knoeledge Test (DKT) instrument developed by Burrough et al (2008), measure to physical activity using the Summary of Diabetes Self Care Activities (SDSCA), measure to family support using Family Support Questionairre, and measure to self efficacy using Diabetes management Self Efficacy Scale (DMSES). The sample siza with simple random sampling method, and data analysis using spearman rank test. Results: The results showed that there was a significant relationship between the level of knowledge and self-management with a coefficient value (r=0.576), a significant relationship between activity ability and self-management with a coefficient value (r=0.612), a significant relationship between family support and self-management with a value of coefficient (r=0.592) and there is a significant relationship between self-efficacy and self-management with a coefficient value (r=0.660). Conclusion: Patients DM Type 2 can be overcome by providing education in every prolanis activity program which is expected to increase knowledge, activity abilities, family support and self-efficacy, so that patients are able to improve self-management well. This intervention is highly recommended for people with Type 2 DM by increasing the frequency of health education and involving the family of diabetes mellitus patients so that patients are able to carry out self-management well.